2023
DOI: 10.1175/wcas-d-22-0049.1
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability in a Tropical Cyclone Risk Model: Philippines Case Study

Abstract: The authors describe a tropical cyclone risk model for the Philippines, using methods that are open-source and can be straightforwardly generalized to other countries. Wind fields derived from historical observations, as well as those from an environmentally-forced tropical cyclone hazard model are combined with data representing exposed value and vulnerability to determine asset losses. Exposed value is represented by the LitPop dataset, which assumes total asset value is distributed across a country followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…(2018, 2020), respectively. The CHAZ model has been used for case studies in Texas (Hassanzadeh et al., 2020), New York (Lee et al., 2022), Mumbai, India (Sobel, Lee, et al., 2019) and the Philippines (Baldwin et al., 2023). Meiler et al.…”
Section: Data Experimental Design and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2018, 2020), respectively. The CHAZ model has been used for case studies in Texas (Hassanzadeh et al., 2020), New York (Lee et al., 2022), Mumbai, India (Sobel, Lee, et al., 2019) and the Philippines (Baldwin et al., 2023). Meiler et al.…”
Section: Data Experimental Design and Methodsmentioning
confidence: 99%
“…The simulated TC activity in CHAZ, at global and basin scales, in both current and projected future climates have been discussed in detail in Lee et al (2018Lee et al ( , 2020, respectively. The CHAZ model has been used for case studies in Texas (Hassanzadeh et al, 2020), New York (Lee et al, 2022), Mumbai, India (Sobel, Lee, et al, 2019) and the Philippines (Baldwin et al, 2023). Meiler et al (2022) found that losses estimated from CHAZ are comparable to those estimated using comparable TC hazard models from Emanuel (2013) and Bloemendaal et al (2020).…”
Section: Synthetic Events From the Chaz Modelmentioning
confidence: 99%
“…They reported that GLM and RF models gave overall unbiased damage predictions across all methods and rarity levels, while KNN consistently under-predicted damage. A vulnerability risk model for the Philippines was put forward by Baldwin et al (2023), in which they assess the vulnerability using the wind field data and total asset value and determine the expected asset loss. In a study, Walsh (2020) proposed a traditional expanded risk assessment using asset losses as the primary metric to measure the severity of a disaster.…”
Section: Related Literaturementioning
confidence: 99%
“…In China, the statistical explanatory power in an empirical model has been found to be significantly higher for TC-induced economic impacts and can increase up to 14-fold when considering wind, inland and coastal floods instead of only wind 3 . However, so far global empirical estimates of TC damages use wind-fields as the only hazard predictor and do not account for floods [4][5][6] . This is particularly problematic as the evidence for a relation between climate change and changes in TC wind speeds is rather weak and subject to large uncertainties 7,8 , while the TC-induced flooding is clearly expected to increase under climate change due to sea level rise amplifying coastal flooding and increasing heavy precipitation extending the pluvial and fluvial flooding 9 .…”
Section: Introductionmentioning
confidence: 99%